Upgrading flax nonwovens: nanocellulose as binder to produce rigid and robust flax fibre preforms - Fortea-Verdejo,M; Lee,K-Y; Zimmermann,T; Bismarck,A (Composites Part A - Applied Science and Manufacturing, 2015)
Typically in flax fibre nonwovens, the fibrous web is mechanically bonded (via entanglement and interlocking of fibres) or thermally bonded (by melting of polymer fibres). Recently, we showed that bacterial cellulose (BC) can be used as effective binder to produce rigid and robust natural fibre nonwovens without the need for polymer binders. Here, we further expand this work to manufacture flax nonwovens by utilising various types of (nano)cellulose, including nanofibrillated cellulose (NFC), BC and pulp fibres. Two preform manufacturing processes are investigated, namely single-step filtration and layer-by-layer filtration. Both BC and NFC serve as excellent binders for loose flax fibres due to their high surface area whilst pulp fibres are a poor binder for flax fibres. This is attributed to the low surface area of pulp compared to BC and NFC, which leads to a lower contact area between flax fibres and pulp. Furthermore, the larger fibre diameter of pulp results in a poorer packing efficiency and, therefore, a higher porosity of 67% compared to preforms made with BC or NFC as binder, which have a porosity of ∼60%. The manufactured preforms possess excellent tensile (View the MathML source, View the MathML source) and flexural (σ = 21.1 MPa, E = 2.2 GPa) properties. Layer-by-layer filtration process results in flax nonwovens, which exhibit even better tensile and flexural properties. This is hypothesised to be due to the better distribution of the fibrous nanocellulose network throughout the preform.